If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(-1) + y = -1 + 1 Multiply 2 * -1 -2 + y = -1 + 1 Combine like terms: -1 + 1 = 0 -2 + y = 0 Solving -2 + y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + y = 0 + 2 y = 0 + 2 Combine like terms: 0 + 2 = 2 y = 2 Simplifying y = 2
| 3y-1-y= | | 15d-20=35 | | 10(5x-3)=120 | | 2(3x-5)=90 | | 5n-35=5(1-7n) | | 8.75+40x=13.25x+509.00 | | x(1.5x+3)=120 | | 8x+12x=268 | | 7-5m=-8 | | X+13=2x-5 | | 2(2x+40)+2(5x)=360 | | 2x+0=x+1 | | 5-3x+1=5x-2 | | 2(0)+y=0+1 | | -4x-39=59-9x | | p=r+p | | 25m+75=30m | | x+29y=180 | | 5x+28=40-7x | | 25-x=18.6 | | 5x+3x-8=2x+16 | | 130d=2r | | 2x+(x+2)=4 | | 22-y=1 | | 30c=75 | | 29y+x=180 | | 5a+4(3a-8)=x-8x | | 10-x=-23 | | -27-11+16+67+15-31= | | -2c-10+5c-25= | | 3(-2+3x)=9x-4 | | t-2c=5 |